KELIMA DAIMYO DALAM PERTEMPURAN SEKIGAHARA PADA FILM ANIME SENGOKU BASARA "THE LAST PARTY”: KAJIAN NEW HISTORICISM - Ekky Puturahman (Japanology: The Journal of Japanese Studies, 2019)
The Sengoku period was a time when Japan was filled with war and chaos. Although so many historical figures in the era that inspired Japanese culture until now. Including also the grup of the strongest daimyo formed by Toyotomi Hideyoshi in his last day. This grup of strongest daimyo potrayal through the Japanese culture was a lot. For examples like in comics, drama series, movies, and anime. One anime that uses the grup as the character is in the Sengoku Basara anime. In the movie version which is Sengoku Basara "The Last Party", the strongest group of daimyo during the Sengoku era of Sekigahara battle that became the background of the film is depicted by different characters. This article will analyze the five daimyo that appear in Sekigahara's battle on the Sengoku Basara "The Last Party" anime movie. Using a descriptive qualitative method, this article will analyze the scene snippets in the film. Using New Historicism, the author analyzes the differences between history and film, the five daimyo who fought in the battle of Sekigahara. Keywords: Daimyo, Go-Tairo,New Historicism, Battle of Sekigahara